An analysis of the Batak Family structure according to Adat and its implication to Christian ethics - Manurung, Kaleb ([n.p.] South East Asia Graduate School of Theology, 1996)
This study is an analysis of the family structure according to adat and its implication to Christian ethics
The Batak tribe has a unique kinship system called the Dalihan na tolu which is not found in the other tribes in the world. The "Dalihan na tolu" (literally three corner-stones) shows the division of the family structure in three functional groups: the "Dongan sabutuha" (the same belly or the same clan), the "Hulahula" (Father-in-law's clan), and the "Boru" (son-in-law's clan). In addition to repenting the Batak Family structure, it also makes up the social organization in the Batak society. It cannot be separated from the Batak adat because it is the basis of the implementation of all adat ceremony
Adat has a very important role in the life of the Batak tribe. It is related to the central occurrences in the life of the community from birth to death for it is a determinant part of the Batak culture embracing all sphere of life. Thus, adat and Dalihan na tolu largely determine each Batak member's attitude, action, behavior, conduct, social relation, and obligation toward another person in his family and in his society. At this point, the study attempts to answer the question on how far the adat and Dahilan na tolu of the Bataks can support the concept of Christian Ethics and at the same time can help forward Christian Ethics to the Batak Christian
In partial fulfillment of the requirements for the degree Master of Theology
A thesis presented to the faculty of the South East Asia Graduate School of Theology (SEAGST)
Thesis (M. Theo) - Divinity School, Siliman University